Corporate sustainability reporting: Linkage of corporate disclosure information and performance indicators - K.A.K. Gnanaweera; N. Kunori (Cogent Business & Management, 2018)
The research was designed to evaluate the determinants of corporate sustainability disclosure practices for 85 Japanese companies listed on Tokyo Stock Exchange (TSE) in the First Section, from 2008 to 2014. The study examined disclosure information from CSR and annual—integrated reports and corporate websites. The study's objective is to measure corporate sustainability disclosure guidelines determination (CSDF rate) and the relationship between CSDF rate and corporate sustainability performance. The content analysis and regression analysis were conducted to examine the research objective. The results of content analysis indicate that listed firms on TSE disclose some extent on environmental, social and economic information but the level of disclosure is vary; CSDF indicator with maximum disclosure level attributed to “Total amount of greenhouse emissions” with 99% disclosing rate and the minimum is the “Index and Grades” with 0%. Moreover, the study finds mixed results conforming to correlation and regression analysis. Similar to some existing studies, sustainability disclosure level and sustainability performance indicators have no strong association. Because there is a weak positive significant linkage among CSDF rate and water consumption, firm's size, and environmental conservation effort. Nevertheless, to be consistent with social values, ensuing the guidelines and the accuracy of the disclosure information are important for corporate sustainability reporting.
Keywords: 650